2020
DOI: 10.26742/panggung.v30i3.1267
|View full text |Cite
|
Sign up to set email alerts
|

Membangun Harmoni Sosial Melalui Musik dalam Ekspresi Budaya Orang Basudara di Maluku

Abstract: This study aims to explain the importance of exploring and communicating the cultural values in the community that can contribute to build social harmony between communities through local music. The study will be conducted by using a qualitative approach that explores and analyzes data both ethic and emic approach to find a description of the culture hidop orang basudara as well as the knowledge, and experience of musicians to build social harmony. The main theory is ethnomusicologist which study relation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Furthermore, a study conducted (Puspitasari et al, 2019) revealed that to discipline students, character strengthening is based on PPK, class culture and community participation. No less interesting research Lestari (2020) concluded that social harmony can be built with music in the cultural expression of the Basudara Maluku people. Regarding methods for resolving conflicts, research results Mohammed (2020) say that the traditional methods of the Aghas ancestors in Iraq can resolve conflicts due to maintaining respect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study conducted (Puspitasari et al, 2019) revealed that to discipline students, character strengthening is based on PPK, class culture and community participation. No less interesting research Lestari (2020) concluded that social harmony can be built with music in the cultural expression of the Basudara Maluku people. Regarding methods for resolving conflicts, research results Mohammed (2020) say that the traditional methods of the Aghas ancestors in Iraq can resolve conflicts due to maintaining respect.…”
Section: Discussionmentioning
confidence: 99%
“…Dalam perspektif yang lebih luas efek positif musik atau lagu bisa juga berfungsi menjadi media guna meningkatkan rasa nasionalisme atau patriotisme. Sesuai dengan pernyataan (Lestari, 2020) bahwa ".. Sebagai suatu negara multikultural, maka negara Indonesia memang perlu mengelola keanekaragaman budayanya secara baik sehingga dapat berkontribusi memperkuat ketahanan nasional". Harus ada gagasan yang mulai serius mengkonsep kemasan musik ini menjadi suatu program pendidikan musik yang secara komprehensif mengatur pentingnya menumbuhkan bibit patriotisme sejak usia dini.…”
Section: Pendahuluanunclassified
“…Selain penelitian di atas, tidak kalah menariknya hasil penelitian (Akbar, 2013) menyimpulkan bahwa metode Triparkoro sangat tepat diterapkan dalam pembelajaran nilai dan karakter kepatuhan untuk Sekolah dasar. Riset (Lestari, 2020) (Kadafi et al, 2021) Berdasarkan berbagai kajian penelitian terdahulu terhadap pemilihan metode dan mempertimbangkan tingkat kebutuhan konselor, maka dalam penelitian ini mengembangkan teknik modeling simbolis bermuatan kesenian tundang untuk meningkatkan harmoni sosial siswa SMP. Penilaian produk dari ahli media, ahli budaya, ahli BK dan calon pengguna menunjukkan kesepakatan sangat tinggi terhadap kebergunaan produk.…”
Section: Gambar3 Link Video Kesenian Tundang Gambar 4 Video Menuturka...unclassified